Isolasi dan Karakterisasi Enzim Phytase Mikroflora Endofitik Tanaman Kedelai (Glycine max (L.) Merril) - DELFITA, RINA (IAIN Batusangkar, 2011)
Two endophytic fungal phytases is isolated from leaf, stem and root fragments collected from soybean and identified as Rhizoctonia sp. and Fusarium verticillioides. The phytase production was induced by phytate in medium used. The crude preparations were used in subsequent characterisation studies, pH and temperature optima and compared to other phytases tested, and is thus a promosing candidate for animal feed applications. This particular phytase retains activity over a wide range pH value characteristic of the digestive tract and could conceivably be more suited to increasingly hinger feed processing temperatures being today, than corresponding phytase from Aspergillus niger. Key words: Endophytic fungal phytase, soybean, Rhizoctonia sp., Fusarium verticillioides, characterisation